Modelling the Denmark Strait overflow during the last interglacial cycle : from regional dynamics to basin wide impacts - Kösters, Frank (2004)
The Denmark Strait overflow is the major gateway for dense water from the Nordic Seas into the North Atlantic and thus it constitutes an important part of the thermohaline circulation under present-day climate conditions. This study focuses on the regional to basin wide dynamics of the Denmark Strait overflow for present-day and Last Glacial Maximum conditions. It contributes to the Research Unit Ocean Gateways located at the University of Kiel which addresses the question how ocean gateways might have affected climate in the past.The volume transport of the overflow is likely to be controlled by hydraulic constraints, thus the transport is set by the relative density contrast between the water masses north and south of the Denmark Strait and the height of dense water above sill level. By using high resolution numerical models it is investigated how the volume transport can be best described using existing hydraulic theories. Hydraulic constraints are shown to be valid over a wide parameter range which allows to transfer this theory to LGM conditions.